Successful Treatment of Mixed Amblyopia with Optic Nerve Hypoplasia (ONH) in an Adult Indonesian Patient - Ria Indah Wahyuningtyas; Niken Indah Noerdiyani; Rozalina Loebis (Vision Science and Eye Health Journal, 2022)
Introduction: Amblyopia significantly contributes to low vision and blindness in adults in an Indonesian rural setting. The treatment of amblyopia, particularly anisometropic and/or strabismic amblyopia, has long been challenging for many clinicians. This study aims to report a promising result of refractive correction, occlusion therapy, and oral citicoline on mixed amblyopia with optic nerve hypoplasia in adult Indonesian patients. Case Presentation: A 20-year-old male with a chief complaint of blurry right eye since one year ago, becoming more severe lately. The patient had been strabismic since his childhood. History of using a -5 concave spherical lens on his RE, with the normal eye on his LE. Visual acuity (VA) of his RE was 3/60 and his LE was 6/30. The RE was deviated, with 30° of exotropia. Nystagmus was also found. Optical coherence tomography (OCT) examination found maculopathy and optic nerve hypoplasia in both eyes. We treated the patient with spectacles to correct the refractive error, occluded his fixing eye, and gave an oral citicoline. Conclusions: Refractive correction and occlusion therapy are still meaningful choices of therapy and have shown to be effective in treating amblyopia, combined with oral citicoline to prevent nerve cell damage. Our case of refractive correction, combined with occlusion therapy and oral citicoline on mixed amblyopia in an adult Indonesian patient, showed good results and a promising post-treatment prognosis with a decrease of exotropia degree and disappearance of nystagmus in just two months.